Focused Ultrasound Mediated Opening of the Blood-Brain Barrier for Neurodegenerative Diseases - Fishman, Paul S.; Fischell, Jonathan M. (Frontiers in Neurology, 2021)
The blood brain barrier (BBB) is an obstacle for the delivery of potential molecular therapies for neurodegenerative diseases such as Parkinson’s disease (PD), Alzheimer’s disease (AD) and amyotrophic lateral sclerosis (ALS). Although there has been a proliferation of potential disease modifying therapies for these progressive conditions, strategies to deliver these large agents remain limited. High intensity MRI guided focused ultrasound has already been FDA approved to lesion brain targets to treat movement disorders, while lower intensity pulsed ultrasound coupled with microbubbles commonly used as contrast agents can create transient safe opening of the BBB. Pre-clinical studies have successfully delivered growth factors, antibodies, genes, viral vectors and nanoparticles in rodent models of AD and PD. Recent small clinical trials support the safety and feasibility of this strategy in these vulnerable patients. Further study is needed to establish safety as MRI guided BBB opening is used to enhance the delivery of newly developed molecular therapies